2001
DOI: 10.1046/j.1440-1754.2001.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy in Victoria, Australia: Mortality and causes of death

Abstract: Children with cerebral palsy are a diverse group and those with a severe motor deficit have a reduced life expectancy. Lung disease remains an important cause of morbidity and mortality for this group. Further information about the causes of death is needed, particularly for those children that die at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 13 publications
(29 reference statements)
7
76
0
1
Order By: Relevance
“…Teresina, PI, 2012 Pulmonary disorders are an important cause of morbidity and mortality in children with CP, predominantly in tetraparetic spastic type or children with GMFCS level V. 22 In studies on the prevalence of respiratory disorders in children with CP, it was found that more than half (56.14 %) of the children studied had pneumonia at some point in their life and 40.35% had disease of the upper airways (rhinitis, sinusitis, sore adenoid, flu) or lower airways (bronchitis, asthma, bronchial dysplasia). 23 Corroborating the findings of this research.…”
Section: Conditions Of Child…mentioning
confidence: 99%
“…Teresina, PI, 2012 Pulmonary disorders are an important cause of morbidity and mortality in children with CP, predominantly in tetraparetic spastic type or children with GMFCS level V. 22 In studies on the prevalence of respiratory disorders in children with CP, it was found that more than half (56.14 %) of the children studied had pneumonia at some point in their life and 40.35% had disease of the upper airways (rhinitis, sinusitis, sore adenoid, flu) or lower airways (bronchitis, asthma, bronchial dysplasia). 23 Corroborating the findings of this research.…”
Section: Conditions Of Child…mentioning
confidence: 99%
“…Their study found that 44.7 percent of the people who died had severe to profound intellectual disabilities, were more inclined to have severe and complex medical disorders and required a great deal of support with core areas such as eating, mobility and incontinence. A Victorian study 32 of children and adults with cerebral palsy, found an increased risk of death due to respiratory disease, particularly in children with severe spastic quadriplegia, epilepsy and intellectual disability. Chaney and Eyman 33 found similar results in a longitudinal study in the United States identifying those most at risk as young, with feeding difficulties, and severe to profound intellectual disability.…”
Section: Mortality Rates In People With Disabilitymentioning
confidence: 99%
“…1,2 Although seizures and disturbances in motor control, cognition, communication, perception, and behavior are the most common features of the disorder, respiratory complications are of concern to a significant proportion of severely disabled patients with CP and represent a major cause of morbidity and mortality. [3][4][5][6][7] Patients with CP are often vulnerable to respiratory complications that can lead to exacerbation. Identifying reliable markers of exacerbation risk could aid physicians in making timely decisions about patient care and recommendations with regard to pulmonary rehabilitation programs.…”
Section: Introductionmentioning
confidence: 99%
“…10 They are also the immediate cause of death in ϳ40% of children with spastic quadriplegia, produce severe distress and poorer health status, and impose a substantial burden on caregivers. 6,7,[11][12][13] Several factors can potentially contribute to the development of respiratory exacerbation in patients with CP, including ineffective cough with airway mucus encumbrance, inability to handle oropharyngeal secretions, swallowing disorders, and gastroesophageal reflux, all conditions that can lead to an increased risk of pulmonary aspiration. In addition, inadequate nasopharyngeal motor tone causing upper-airway obstruction and obstructive sleep apnea syndrome, scoliosis deformities leading to obstruction of the lower-lobe bronchi, and poor nutritional status may further compromise respiratory function.…”
Section: Introductionmentioning
confidence: 99%